IMPROVING FRACTIONS LEARNING OUTCOMES THROUGH PBL-BASED MATH GAMES AND POWTOON VIDEOS AT SDN 37 LUBUKLINGGAU - vira muspita; lucy purwasi (CV Grasta Glory, 2026)
Problem-Based Learning (PBL) is a student-centered instructional approach that emphasizes the use of real-life problems to develop students’ higher-order thinking skills and active involvement in the learning process. This study aimed to examine the effectiveness of the Problem-Based Learning model in improving students’ academic achievement and learning engagement, particularly in the cognitive domain. The research employed a classroom action research design involving 17 fifth-grade students of MIN 26 Hulu Sungai Utara during the odd semester of the 2022/2023 academic year. Data were collected through observation sheets to measure student participation and written tests to assess learning outcomes. The results revealed that in the pre-cycle stage, the students’ average score was 68.12, with a classical mastery level of 47%, where only 8 out of 17 students achieved the minimum passing grade of 65. After the implementation of PBL, students’ learning outcomes improved progressively. In Cycle 1, the average score increased to 75.29 with a classical mastery of 70.59%, while in Cycle 2, the average score further rose to 78.82, and classical mastery reached 82.5%, with 14 students achieving the minimum passing grade. These findings indicate that the Problem-Based Learning model is effective in enhancing students’ academic achievement and engagement in learning.